A working man [videorecording (Blu-Ray)] - Ayer, David; Stallone, Sylvester; Statham, Jason, 1967-; Flemyng, Jason; Niniże, Merab, 1965-; Osinski, Maximilian; Falkow, Cokey; Peña, Michael, 1976-; Harbour, David, 1975-; Dixon, Chuck, 1954- (MGM, 2025)
Levon Cade left his "profession" behind to live a simple life working construction and spending time with his daughter. But when his boss's teenage daughter vanishes, he's called upon to re-employ the skills that made him a legendary figure in the shadowy world of black ops. Levon's hunt for the missing college student takes him to the heart of a sinister criminal conspiracy creating a chain reaction that will threaten his new way of life.